MANIPULATION OF SINK-SOURCE RELATIONS IN TRANSGENIC PLANTS - Sonnewald, Uwe; et al. (1994)
Since 1980, the use of transgenic plants in modern plant science has become a powerful tool to study whole plant physiology. In this review, we try to summarize the data obtained in the field of photoassimilate partitioning. Attempts to study sink-source interactions concern factors which might limit sink strength and source capacity. Transgenic plants have been used to manipulate the sucrose to starch ratio in order to produce plants with higher sucrose levels in their source leaves. Alterations in partitioning were achieved by manipulating Calvin cycle enzymes, transport proteins and sucrose biosynthetic enzymes. The ability of sink tissues to attract photoassimilates has been altered by either increasing or decreasing sucrose hydrolytic activities. The increase of sucrose hydrolysis was achieved by creating transgenic potato plants with tuber specific yeast-derived invertase. Decreased sucrose utilization was achieved by antisense inhibition of sucrose synthase in potato tubers.
Keywords: ANTISENSE INHIBITION; METABOLIC DESIGN; PHOTOASSIMILATE PARTITIONING; PHOTOSYNTHESIS; SINK-SOURCE; TRANSGENIC PLANTS